INVESTIGATION OF HEAT UTILIZATION EFFICIENCY IN SUCTION AND EXHAUST VENTILATION SYSTEMS - A. N. Kuzovlev; V. V. Moroz (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a possibility  to use a  thermal pump and heat-exchange device  in  the ventilation system  for heat utilization of exhaust air. An  influence of air characteristics on  energy  efficiency  of heat-utilizing installations has been shown in the paper. Specific feature of the thermal pump application is the fact hat a source of secondary heat has higher temperature than a consumer. The paper contains results of thermal pump and heat exchange device parameters, hat characterize their efficiency while being applied in a ventilation system.